Ion-mediated cross-linking of biopolymers confined at liquid/liquid interfaces probed by in situ high-energy grazing incidence X-ray photon correlation spectroscopy - Amadei, Federico; Thoma, Judith; Czajor, Julian; Kimmle, Esther; Yamamoto, Akihisa; Abuillan, Wasim; Konovalov, Oleg V.; Chushkin, Yuriy; Tanaka, Motomu (The journal of physical chemistry. B, Biophysics, biomaterials, liquids, and soft matter, 2020)
As manifested in biological cell membranes, the confinement of chemical reactions at the 2D interfaces significantly improves the reaction efficacy. The interface between two liquid phases is used in various key processes in industries, such as in food emulsification and floatation. However, monitoring the changes in the mechanics and dynamics of molecules confined at the liquid/liquid interfaces still remains a scientific challenge because it is nontrivial to access the interface buried under a liquid phase. Herein, we report the in situ monitoring of the cross-linking of polyalginate mediated by Ca2+ ions at the oil/water interface by grazing incidence X-ray photon correlation spectroscopy (GIXPCS). We first optimized the reaction conditions with the aid of interfacial shear rheology and then performed GIXPCS using a high-energy synchrotron X-ray beam (22 keV) that guarantees sufficiently high transmittance through the oil phase. The intensity autocorrelation functions implied that the formation of a percolated network of polyalginate is accompanied by increasing relaxation time. Moreover, the relaxation rate scales linearly with the momentum transfer parallel to the interface, suggesting that the process is driven by hyperdiffusive propagation but not by Brownian diffusion. Our data indicated that high-energy GIXPCS has potential for in situ monitoring of changes in the dynamics of polymers confined between two liquid phases.
Gesehen am 23.11.2020